Peripheral Perception And its Relation With The Need for Cognition for The University Students (Journal of the College of Education for Women, 2019)
The most important topic for psychologist generally is factor of education and it's active tools because learning needs active perception for stimulus that recived by the educator and give it avalue and meaning , Need for cognition isvery important in the various daily fields of life , especially in learning and teaching and the academy work , it help with shifting the learning level for people , and icreas the intense and challenge between themThe research endeavored to achieve the following aim :1- Measuring the level of peripheral perception for the university student .2- Measuring the level of need for cognition for the university student .3- Measuring the level of peripheral perception for the university student according to gender .4- Measuring the level of need for cognition for the university student according to gender .5- Finding the relationship between both variables (peripheral perception) and (need for cognition) for the university students .The two scales are applied to sample consisted of (100) male and female students of the university student / al jadriya compound exclusively for reasons mentioned with in the current research , and for psychometric properties of the test of peripheral perception it has high validity and reliability and to extract the psychometric properties of the scales of need for cognition is applied to sample consisted of (200) male and female students of the university students , after applying both research tools to the sample and data analysis , the study has arrived at the following result . The sample of the research males have (field of vision , power of focus , divided attention , reaction time to stimuli) more than the females , but there was no differences between males and females according to (emotional maturity) . The sample of the research have higher need for cognition . And there is appositive relationship between (field of vision and emotional maturity) and the variable of need for cognition and there is negative relationship between (power of focus , divided attention , reaction time to stimuli) and the variable of need for cognition .